PENGARUH KONFORMITAS TEMAN SEBAYA TERHADAP PERILAKU BULLYING PADA PESERTA DIDIK FASE E DI SMAN 1 BATANG KAPAS - Ulfa Nofutri; Rila Rahma Mulyani; Suryadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the presence of students who mocked their classmates because their friends had body odor, there were students who nudged their friends' shoulders and said harsh words, there were students who obeyed the group leader because they wanted to control the group, there were students who did not respect other people's opinions. This study aims to determine: 1) Peer conformity in Phase E students at SMAN 1 Batang Kapas, 2) Bullying behavior of Phase E students at SMAN 1 Batang Kapas, 3) The effect of peer conformity with bullying behavior in Phase E students of SMAN 1 Batang Kapas.This study uses quantitative research methods. The population was 30 sampling techniques Total Sampling. The instrument used in this research is a questionnaire. Data analysis in this study is a percentage and simple linear regression. The results of this study showed: 1) peer conformity of students at SMAN 1 Batang Kapas is in a fairly high category. 2) bullying behavior of Phase E students in SMA Negeri 1 Batang Kapas is in a fairly high category. There is an influence of peer conformity with bullying behavior in Phase E students at SMAN 1 Batang Kapas with a very low coefficient with a value of 0.016. Based on the results of this study, it is recommended to students to improve aspects of peer conformity, namely to increase cohesiveness, agreement, and obedience in a group so that it becomes better. Conversely, it can also be seen in aspects of bullying behavior, namely physical bullying, verbal bullying, and mental/psychological bullying so that students can reduce bullying behavior. In addition, counseling teachers can minimize the occurrence of bullying behavior in schools by providing information services about the dangers of bullying behavior.